Time is money - how much money is time? Interest and inflation in competition law actions for damages - Eckart Bueren; Kai Hüschelrath; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Public and private action against cartels is an internationally recognized cornerstone of antitrust enforcement. Effective private enforcement requires that cartel victims can receive (at least) full compensation for the harm suffered. Academics and competition authorities support this goal with guidance for the calculation of cartel damages. However, they usually neglect that the prosecution of competition law infringements can be very time-consuming, so that it often takes several years until cartel victims obtain damages. Interest and inflation are thus two key drivers of adequate compensation. This paper is the first to provide a comparative law and economics perspective on this topic: We investigate how various legal systems treat interest and inflation as part of competition law actions for damages, and, using real-world data from the lysine cartel, simulate the economic differences, which turn out to be substantial. By comparing and evaluating the regulatory techniques, our paper provides important insights for regulators, litigation practitioners and the ongoing reform discussions in the EU and the US. At the same time, our approach is a first step towards a quantitative comparative law and economics analysis of the law on interest in the field of tort law.
urn:nbn:de:bsz:180-madoc-358510
Keywords: K21; L41; L61; 330; Antitrust policy; cartels; private enforcement; damages; interest; inflation